Clinical Efficacy of Dioctahedral Smectite in the Complex Therapy of Acute Intestinal Infections in Children - A. A. Novokshonov; N. V. Sokolova (LLC "Diagnostics and Vaccines", 2016)
The article presents the results of research on the study of clinical effectiveness and impact on intestinal microbiocenosis dioctahedral smectite (Neosmektin®) of acute intestinal infectious of bacterial, viral, and mixt etiology. The clinical studies have shown that the additional inclusion in the complex therapy for children this enterosorbent has a pronounced detoxification and antidiarrheal effect, reducing the duration of the acute period of the disease increases sanitize effectiveness of the therapy against pathogens and contributes to the normalization of microbiocenosis intestine.